A study on alcohol dependence and it’s determinants among male patients attending a tertiary care hospital, Kolkata - Mukherjee, Sumit; Ghosh, Sayanti (Asian Journal of Medical Sciences, 2022)
Background: Alcohol intake is one of the major substance abuse and the problems of alcoholism is present throughout the world. There are some fundamental differences regarding socio-demographic profile, age of onset of drinking, and the nature of drinking etc. Aims and Objectives: This study was conducted to find out the association of several determinants like onset and duration of drinking, family history and role of biomarkers like Gamma-Glutamyl transferase (GGT), Mean corpuscular volume (MCV) with severity of alcohol dependence. Materials and Methods: It was a hospital based cross-sectional and observational study. Screening and assessment of alcohol dependence was done by using scales like AUDIT and Alcohol dependence scale. Semi-structured questioner was used for assessing sociodemographic data for the total sample of 100 patients. 65 cases were selected finally after screening by AUDIT scale. GGT and MCV estimation was done for the finally selected cases along with healthy controls. Descriptive statistical analysis was done for obtaining results. Results: Findings suggest that early onset of drinking that is 17.14 years is associated with severe level of alcohol dependence. Study shows that family history of alcohol use is a predictor of developing alcohol dependence. Biomarkers like GGT, MCV had shown significant elevation for cases of severe dependence. Conclusion: The burden of alcohol use is growing alarmingly in India and before it turns out to be a giant monster encroaching upon youths, we need to focus our attention in curbing this problem by diagnosing and treating alcohol dependent patients and using preventive measures, to not allow development of dependence at all.